2017
DOI: 10.1080/1331677x.2017.1311228
|View full text |Cite
|
Sign up to set email alerts
|

Domestic and cross-border returns to bidders in acquisitions into the E.U.

Abstract: The article analyses shareholders returns of acquiring banks in the United Kingdom (U.K.) i.e., when U.K. banks acquire domestic banks and when U.K. banks acquire cross-border banks within the European Union (E.U.). The article includes 75% sample of the total population of bank to bank domestic acquisitions within the U.K. and crossborder acquisitions within the E.U. from 2006 until 2013. The article comes to the conclusion, by the means of event study methodology, that the shareholders returns of acquiring b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…However, the evidence with regard to the outcomes of acquisitions is mixed (Selçuk et al, 2016). There are studies that find positive outcomes (e.g., Golubov and Xiong, 2020;Powell and Stark, 2005), others that find negative outcomes (Chaudary and Mirza, 2017;Yeh and Hoshino, 2002), and yet others that report insignificant findings (Moeller and Schlingemann, 2005). Although the role of emerging markets in world investment flows has increased tremendously (Stiebale and Trax, 2011;Othchere and Oldford, 2018), the majority of studies about M&As are based on developed markets (e.g., Jensen-Vinstrup, Rigamonti, and Wulff, 2018;Li, Qiu, and Shen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence with regard to the outcomes of acquisitions is mixed (Selçuk et al, 2016). There are studies that find positive outcomes (e.g., Golubov and Xiong, 2020;Powell and Stark, 2005), others that find negative outcomes (Chaudary and Mirza, 2017;Yeh and Hoshino, 2002), and yet others that report insignificant findings (Moeller and Schlingemann, 2005). Although the role of emerging markets in world investment flows has increased tremendously (Stiebale and Trax, 2011;Othchere and Oldford, 2018), the majority of studies about M&As are based on developed markets (e.g., Jensen-Vinstrup, Rigamonti, and Wulff, 2018;Li, Qiu, and Shen, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the investment impact of marketing authorization, we use the event study methodology, and it helps evaluate the effect of new information on marketable assets beyond usual expectations. Examples may include gains for bidders ( Chaudary and Mirza, 2017 ), risk pricing ( Nguyen et al., 2019 ), rating changes ( He and Schiereck, 2019 ), and performance of bond issuers ( Berninger et al., 2021 ). If the introduction of vaccines has an investment impact, it should result in abnormal returns for the fund investors.…”
Section: Research and Methodologymentioning
confidence: 99%
“…where k i is the rank of the i-th stock, and s(k) is the standard deviation of the portfolio mean abnormal rank. Corrado (1989), and Campbell and Wasley (1996) have shown that nonparametric tests are more powerful for detecting abnormal performance. Another advantage of these tests is that they do not depend upon the normality assumption.…”
Section: Event Study Methodologymentioning
confidence: 99%